AN ANALYSIS OF PEPPER EXPORTS AND IMPORTS ON ECONOMIC GROWTH IN INDONESIA - Rini Permata; Ichsan Ichsan (LPPM Universitas Malikussaleh, 2022)
This study examines the effect of pepper exports and imports on economic growth in Indonesia during the period of 1990-2019. This study uses secondary data from 1990 to 2019 accessed on www.bps.go.id. The data analysis method used is Multiple Linear Regression Analysis using Software Eviews 9. The results shows that pepper exports have no significant effect on economic growth in Indonesia, and pepper imports have a negative and significant effect on economic growth in Indonesia. This study suggests that government pay full attention and support to Indonesian pepper farmers so that the production and quality of pepper will increase in the future and can reduce pepper imports.